A Case Study of Activity Based Costing for Hotline Furniture Manufacturers Sdn. Bhd - Teh, Su Kang (1999)
Activity Based Costing, a new costing method to compute costing for a product in a more appropriate way compared to Traditional Cost Accounting in this new manufacturing environment which is capital intensive. The significant different between Activity Based Costing and Traditional Cost Accounting is overhead absorption basis. Activity Based Costing charge out manufacturing overhead based on activity that related to the production whereas Traditional Cost Accounting charge out manufacturing overhead based on the production volume of the product. In this competitive market where consumer demand for high quality product with low price, Hotline Furniture Manufacturers Sdn Bhd has no other choice to implement more appropriate costing system to ensure that the factory price its product which can be compete in the market. However, at this initial stage, Activity Based Costing were only applied to one of the sales contract that going to be taken by the Company. As the Company has to decide whether to take up the sales contract, costing for the product under the sales contract was undergone a costing review. By implementing· Activity based Costing method, the Company might decide to take up the sales contract worth USD2.0 million as the product price has been over-priced for the past